Cyclic nucleotide-gated ion channel gene CNGC3 positively regulates immunity against Sclerotinia sclerotiorum in Arabidopsis - LIU Mengjiao; YI Hang; CAI Xinzhong (浙江大学学报. 农业与生命科学版)
Functions and mechanisms of cyclic nucleotide-gated ion channel (CNGC) in plant immunity against necrotrophic pathogens remain largely unknown. In this study, we explored the functions of AtCNGC3 in immunity against Sclerotinia sclerotiorum, a typical necrotrophic pathogen, through identifying subcellular localization of its expression product, defining its expression patterns and genetically analyzing its function in immunity. The results showed that AtCNGC3 protein was localized in plasma membrane. AtCNGC3 was highly expressed in all analyzed tissues of Arabidopsis thaliana without showing any tissue specificity. Sclerotinia sclerotiorum inoculation strongly and constantly induced the expression of AtCNGC3 gene. The Atcngc3 mutant plants were more susceptible to S. sclerotiorum, while AtCNGC3 overexpression (AtCNGC3-OE) plants exhibited enhanced resistance to S. sclerotiorum, indicating that AtCNGC3 positively regulates the resistance to S. sclerotiorum. Seedlings soaking with Arabidopsis thaliana plant elicitor peptide 1 (AtPep1) could rapidly induce AtCNGC3 gene expression. AtPep1-elicited reactive oxygen species (ROS) burst was weakened in the Atcngc3 mutant seedlings while enhanced in the AtCNGC3-OE plants, demonstrating that AtCNGC3 positively regulates AtPep1-induced ROS burst. Collectively, our results reveal that AtCNGC3 positively regulates immunity against the necrotrophic fungal pathogen S. sclerotiorum in Arabidopsis, thereby providing some insights into the functions of CNGC in plant immunity.